The nature of agricultural markets: Output marketing in Tanzania - Basile Boulay (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2015)
This paper uses the three available waves of data from the Tanzanian National Panel Surveys to study different agricultural markets. We use crop level data to analyse the factors influencing farmers' choice between selling to market or retaining output for household consumption, allowing for market differences across crops. We estimate probit models for each wave and crop (or crop categories). Results show that there is not a homogeneous market for all crops, and the entrance decision is driven by different factors. Contemporaneous and lagged prices as well as use of storage facility are important variables that influence the decision to enter a market differently across crops. Entering the markets for subsistence crops such as maize or cassava can be the result of economic distress, supporting a 'forced commerce' hypothesis. The market for export crops responds to price and expectation mechanisms and is closer to the conception of agricultural markets in standard theory.
Keywords: Q12; Q13; R20; O13; 330; agricultural economics; Tanzania; applied econometrics; crop sales